Hospital Responsibilities in Storing Electronic Medical Record Documents - Sugianto Prajitno; Mokhamad Khoirul Huda; Asmuni (JILPR Journal Indonesia Law and Policy Review, 2023)
Medical records in hospitals are data for compiling health information and every health service and every health service, whether providing outpatient or inpatient services, is required to make a medical record and sanctions are imposed for those who violate it in accordance with applicable laws and regulations. The aim of this research is to analyze the norms for storing and destroying manual medical record documents and to analyze the legal responsibility of hospitals for storing electronic medical records in hospitals. The type of research used in this research is legal research. This type of research is carried out by examining legal norms in applicable laws and regulations related to guidelines and codes of ethics for a profession, especially in this case, medical laboratory technology experts in providing health services. Specifically, the type of research is normative juridical or doctrinal research. The findings of this research are that the legal responsibility of hospitals for storing electronic medical records in hospitals has been regulated by Minister of Health Regulation No. 24 of 2022, while the responsibility of hospitals in implementing electronic medical records is also outlined in the Ministry of Health in the form of ministerial supervision through the director general. If deviations occur, administrative sanctions will be given in the form of a warning or revocation of accreditation status.